차전초 에탄올 추출물의 항산화 효능 - 김유진; Yoo-jin Kim; 김소영; So Young Kim; 정미진; Mi Jin Jeong; 이은탁; Un-tak Lee; 추성태; Sung-tae Choo; 윤석나; Seok Na Youn; et al. (大韓本草學會誌, 2018)
Objectives : Butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA) were well known as anti-oxidant, but they were limited to use because of toxicity. So, many studies are being done to develope natural anti-oxidant. Total phenolic and flavonoid contents along with total antioxidant capacity of the ethanolic extract of Plantaginis Herba (PH) were evaluated to explore the reliable and potential sources of novel natural antioxidants. Methods : Total polyphenol contents and total flavonoid contents in PH ethanol extract were determined by colorimetric method. And DPPH(1.1-diphenyl-2-picrylhydrazyl), ABTS(2'-azino-bis (3-ethylbenzothiazoline-6-Surfonicacid)) free radical scavenging capacity and reducing power inhibition activities of PH ethanol extract were measured at 100, 500, 1000, 5000 ㎍/㎖ concentrations by spectrometric assay. Results : The total polyphenol contents and total flavonoid contents of the extract were 161.99 ㎎/g, 144.05 ㎎/g, respectively. Also, DPPH, ABTS free radical scavenging capacity and reducing power of PH ethanol extract in treated concentrations (100, 500, 1000, 5000 ㎍/㎖) increased dose dependently. In particular, DPPH free radical scavenging capacity of PH ethanol extract from 500 ㎍/㎖ was significantly increased compared to positive control (BHA). ABTS free radical scavenging capacity of PH ethanol extract from 1000 ㎍/㎖ was significantly higher than BHA. Also, reducing power showed that PH ethanol extract from 500 ㎍/㎖ was significantly increased compared to BHA. Conclusions : These results suggest that PH ethanol extract has effects to scavenge free radicals, thus PH has potential and applicable benefits for development of materials and products to have anti-oxidation functions.